Modelling of distributional impacts of energy subsidy reforms an illustration with Indonesia - Durand-Lasserve, Olivier (OECD Environment Working Papers, 2015)
This report develops an analytical framework that assesses the macroeconomic, environmental and distributional consequences of energy subsidy reforms. The framework is applied to the case of Indonesia to study the consequences in this country of a gradual phase out of all energy consumption subsidies between 2012 and 2020. The energy subsidy estimates used as inputs to this modelling analysis are those calculated by the International Energy Agency, using a synthetic indicator known as "price gaps". The analysis relies on simulations made with an extended version of the OECD's ENV-Linkages model. The phase out of energy consumption subsidies was simulated under three stylised redistribution schemes: direct payment on a per household basis, support to labour incomes, and subsidies on food products.